Pemanfaatan Permainan Tradisional Sebagai Media Pembelajaran Edukatif pada Siswa Sekolah Dasar - Muhammad Rusli; Jud Jud; Suhartiwi Suhartiwi; Marsuna Marsuna (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2022)
Tujuan dari pengabdian kepada masyarakat yaitu untuk mengetahui pemanfaatan olahraga tradisional sebagai media pembelajaran edukatif pada siswa sekolah dasar. Siswa sekolah dasar mempunyai banyak kendala di era modern ini banyak siswa yang sudah tidak paham dengan olahraga tradisional bagaimana bentuk dan cara  pelaksanaannya, jadi tim pengabdian memanfaatkan olahraga tersebut sebagai media untuk pembelajaran edukatif, dengan menggunakan alat-alat permainan bersifat tradisional, sehingga akan menimbulkan kegembiraan dan jiwa sosial anak, meningkatkan kemampuan motorik, menjalin kekompakan, mengasah mental dan yang paling utama meningkatkan kondisi fisik, sehingga dapat mencapai kebugaran jasmani siswa untuk terus semangat dalam belajar dan beraktivitas. The process of implementing community service activities uses socialization and demonstration methods which are directly directed by the service team explaining and exemplifying one by one the easy games, namely terompah panjang and lari balok, as well as difficult games, namely egrang for the use of traditional sports in learning through traditional games, as well procedures for the rules of the game or its implementation. Setelah siswa paham dengan teknik yang akan dipraktikkan tim peneliti membagi beberapa kelompok dari siswa yaitu kelompok yang mempraktikkan terompah panjang, egrang maupun lari balok. kegiatan yang dilaksanakan siswa akan lebih paham tentang olahraga tradisional dan akan meningkatkan kekompakkan, keseimbangan, kelincahan, kecepatan dan koordinasi. Kemudian siswa dapat langsung mempraktikkan secara mandiri dan di awasi oleh tim pengabdian. Tahap evaluasi yaitu mengadakan perlombaan yang diikuti oleh beberapa kelompok siswa yang dilakukan dengan penuh kegembiraan, dan tim yang menang akan mendapatkan hadiah atau bingkisan dari tim pengabdian. Berdasarkan hasil pengabdian siswa sangat antusias dalam pelaksanaan olahraga tradisional. Utilization of Traditional Games as Educative Learning Media for Elementary School Students The aims of community service is to find out the use of traditional games as an educational learning medium for elementary school students. Elementary school students have many obstacles in this modern era, many students are no longer familiar with traditional sports how they are formed and implemented, so the service team uses the sport as a medium for educational learning, using traditional game tools, so that it will cause joy and social spirit of children, improve motor skills, establish cohesion, hone mentally and most importantly improve the condition  physical, so as to achieve physical fitness of students to continue to be enthusiastic in learning and activities. The process of implementing service activities uses socialization and demonstration methods which are directly directed by the service team to explain and exemplify one by one for the use of traditional sports in learning terompah panjang, egrang and lari balok, as well as procedures for game rules or implementation. After the students understood the techniques to be practiced, the research team divided several groups of students, namely the group that practiced terompah, egrang and block running. The activities carried out by students will understand more about traditional sports and will create cohesiveness, balance, agility, speed and improve coordination and. Then students can directly practice independently and be supervised by the service team. The evaluation stage is to hold a competition that is attended by several groups of students which is carried out with happines and the winner team in the competition the service team provides gifts to the participants as prizes from winning. Based on the results of the service, students are very enthusiastic in implementing traditional sports.